Examining the effects of perceived usefulness, perceived ease of use, shopping orientation, and online trust on online purchase intention - Sufian, Atirah; Lim, Shu En; Azman, Hartini; Mohd Zamri, Alif Ziyad (Research and Scientific Innovation Society, 2026)
Despite the rapid growth of e-commerce, online purchase intention remains inconsistent, as many consumers continue to hesitate due to concerns related to system usefulness, ease of use, trust, and individual shopping preferences. Understanding these factors is crucial for online retailers seeking to enhance consumer engagement and purchase behaviour. Accordingly, this study examines the factors influencing online purchase intention, focusing on perceived usefulness, perceived ease of use, shopping orientation, and online trust. The objective of this research is to investigate how these variables affect consumers’ decisions to make purchases through online platforms in Malaysia. A quantitative research approach was adopted, involving 200 respondents. Pearson correlation analysis, reliability testing, and multiple regression analysis were employed to examine the relationships between the independent variables and online purchase intention, as well as to determine the relative influence of each factor. The findings reveal that perceived usefulness, perceived ease of use, shopping orientation, and online trust all have significant and positive relationships with online purchase intention. Among these factors, perceived usefulness emerged as the most influential predictor, indicating that consumers are primarily motivated by the functional benefits and value provided by online shopping platforms rather than by ease of use alone. This study supports the Technology Acceptance Model (TAM) and extends it by incorporating shopping orientation and online trust as key determinants of online purchase intention within the Malaysian context. From a managerial perspective, the findings suggest that online businesses should prioritise enhancing platform usefulness, strengthening trust-building mechanisms, and tailoring platform features to different shopping orientations in order to increase consumers’ intention to purchase online. Future research may explore these relationships across different cultural or economic contexts to improve the generalisability of the findings.